PENEGAKAN HUKUM TINDAK PIDANA PROSTITUSI SECARA ONLINE DI WILAYAH HUKUM POLISI RESOR KOTA PEKANBARU - Venny Humairah; Emilda Firdaus; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Online prostitution is prostitution or an activity which makes a person as an object for traded via electronic or online media, media that is in use, such as blackberry massanger, whatsapp and facebook. In other words, here the people in charge to be able to respect the norms and values contained in the lives of the people in because cases of online prostitution can destroy the future of the nation as their cases were found with offenders who were aged teenager and is still a lack of traction regulation Legislation to entrap prostitutes.In writing this essay, the writer used juridical sociological namely a review of secondary data in the form of legislation, as well as the results of the legal scholars, such as books related to the subject matter to then proceed with research on primary data (data obtained directly from respondents) . From the research problem there are two things that can be inferred. Law enforcement against criminal acts of prostitution online in Jurisdiction Pekanbaru City Police has been running and has undertaken a series of actions of investigation and inquiry to uncover cases of online prostitution. From the results of investigations conducted by the Police Resort city of Pekanbaru in the know that the perpetrators of online prostitution utilize massanger and whatsapp blackberry. Building partnerships with the broader community partnerships in the wider community to help pave the accounts relating to perjual-belian women through online media.Suggestions Author, First Law enforcement against criminal acts of prostitution online by City Police Pekanbaru should be done in a more intensive and thorough, because prostitution online is spreading very fast and the activities or transactions done through electronic media so that the police have a hard in terms of searching for evidence and peroses investigation was difficult. Second, In the hope to the community to better care for these activities online prostitution so as to facilitate the Pekanbaru City Police in tackling it..Keywords : Law Enforcement - Crime of Prostitution - Online